Higher percentage of CD34 + CD38− cells detected by multiparameter flow cytometry from leukapheresis products predicts unsustained complete remission in acute myeloid leukemia. Issue 3 (March 2015) - Plesa, Adriana; Elhamri, Mohamed; Clapisson, Gilles; Mattei, Eve; Gazzo, Sophie; Hequet, Olivier; Tigaud, Isabelle; Michallet, Mauricette; Dumontet, Charles; Thomas, Xavier
Abstract: Relapse in acute myeloid leukemia (AML) after chemotherapy reflects the persistence of resistant leukemia stem cells (LSCs). These cells have been described in the CD34 + CD38− cell fraction. Leukapheresis products were harvested in 123 patients in morphological complete remission and analyzed by multiparameter flow cytometry. The CD34 + CD38− cell population showed a prognostic impact on survival. Median event-free survival (EFS) was 8.2 months (3-year EFS: 29%) for those with a higher percentage of CD34 + CD38− versus 91.9 months (3-year EFS: 62%) for those with a lower percentage for the entire cohort. These differences were confirmed in patients undergoing autologous stem cell transplant, with median EFS of 7.3 months versus 91.1 months (3-year EFS: 31% vs. 70%). Higher proportions of CD34 + CD38− cells were associated with adverse cytogenetics and with earlier relapses. Higher percentages of CD34 + CD38− cells in apheresis products reflect inadequate in vivo purging and reliably distinguish samples enriched in LSCs from those involving mainly normal cells.